The impact of Disability Studies curriculum on education professionals’ perspectives and practice: Implications for education, social justice, and social change - Pearson, Holly; Cosier, Meghan; Kim, Joanne J.; Gomez, Audri M.; Hines, Carol; McKee, Aja A.; Ruiz, Litzy Z. (Disability Studies Quarterly, 2016)
As a field, Disability Studies has gained ground in the past few decades by highlighting alternative ways of thinking about disability as a social, cultural, and political phenomenon. As more education professionals pursue advanced degrees with a Disability Studies framework, there is a need to understand how, if at all, Disability Studies influences their perspectives and practices. This study employed semi-structured interviews with nine doctoral students enrolled in a Doctorate of Philosophy in Education program that used the framework of Disability Studies, who are also practicing education professionals, to explore how gaining knowledge about Disability Studies impacted their daily work in the field of education. Through their experiences, they indicated that Disability Studies has transformed their conceptualization of disability, their practices, and themselves.